Sustainable Built Environments: Building Information Modeling, Biomaterials, and Regenerative Practices in Mexico - Fabiola Colmenero Fonseca; Ramiro Rodríguez Pérez; Juana Perlaza Rodríguez; Juan Francisco Palomino Bernal; Javier Cárcel-Carrasco (Buildings, 2024)
This article explores how the construction sector can significantly contribute to minimizing its environmental impact through reuse and recycling practices, in rehabilitation or new construction projects. This research focuses on implementing BIM methodology alongside biomaterials, 3D modeling, and digitization in compliance with the Green Building Code. Two case studies located in Jalisco and Querétaro (Mexico) are examined through a comparative analysis. The simulations are carried out in different geographical areas with two construction systems that allow us to see the output similarities. The results show the clear advantages of biomaterials over traditional materials such as concrete. The construction materials are shown to determine their operational energy consumption. From an economic point of view, this study supports data regarding lower energy costs, and a significant reduction in CO2 emissions is observed. In conclusion, both the models and simulations, along with the Toolkit, highlight the benefits of biomaterials over conventional industrial materials.